Spatial Decision Support System Model for Economic Resilience in East Java Province - Firman Afrianto; Annisa Dira Hariyanto (East Java Economic Journal, 2024)
Economic resilience has many dimensions and aspects to consider. The complexity of studying resilience ultimately requires simplification in the form of a model that can be applied in spatial decision-making. This study aims to find a model and simulation of economic resilience policy priorities for East Java Province in the form of a Spatial Decision Support System. The calculation is done by applying the TOPSIS algorithm on the vectorMCDA plugin in a geographic information system and qualitative descriptive analysis. The results of the calculation indicate that the focus of economic resilience policy is on the aspects of recovery and transformational innovation, while the ideal resilience policy alternative is the most appropriate priority policy alternative.